Re-establishing Order in Brunei: The Introduction of the British Legal System during the Early Residential Period - Mansurnoor, IIK Arifin (Islamic Studies, 2013)
By the end of the nineteenth century, Brunei had lost much of its former power and territories. Not surprisingly, Western adventurers, visitors and, officials who reported on Brunei had little to say about its economic, social, judicial and political grandeur. Indeed, the declining state has been described as a ‘dying kingdom.’ Under such conditions, is it surprising that British officials eventually argued for the promotion of government ‘conducted on enlightened lines’ to relieve the population from ‘the distress which . . . the cruelty and heartlessness’ of their owners had been imposed upon them?